DEVELOPMENT OF A PROTOTYPE MICRO WIND ENERGY SYSTEM WITH ADJUSTABLE BLADE PITCH FOR EXPERIMENTATION PURPOSES AT LABORATORY LEVEL - Ashraf, M. M.; Malik, T. N.; Iqbal, M. (The Nucleus, 2014)
In this paper, the design of an efficient, operational and productive model of micro wind energy system has been proposed for experimentation purposes at laboratory level. The proposed model constitutes a proficient Horizontal Axis Wind Turbine (HAWT) model with multi-stage pulley system as a gear box and adjustable blade pitch. The wind turbine is coupled to Axial Flux Permanent Magnet Generator (AFPMG). The power density parameter of fabricated AFPMG has been improved to 35.7%. A wind tunnel is placed in front of wind turbine which behaves as the operational source of wind for proposed model. Multiple case studies: demonstration of different components of wind energy system, effect of variable wind speed, effect of variable blade pitch, effect of variable electrical loading, effect of variable pulley ratio, voltage regulation of AFPMG, runaway speed test of HAWT and peripheral speed test of AFPMG are successfully performed on this model. The results obtained from experiments show that proposed model is well suited for experimentation purposes at laboratory level.